Markedly enhanced visible-light photocatalytic H2 generation over g-C3N4 nanosheets decorated by robust nickel phosphide (Ni12P5) cocatalysts. Issue 6 (19th January 2017) - Wen, Jiuqing; Xie, Jun; Shen, Rongchen; Li, Xin; Luo, XingYi; Zhang, Hongdan; Zhang, Aiping; Bi, Guican
Abstract : Ni12 P5 modified g-C3 N4 photocatalysts exhibit significantly enhanced photocatalytic H2 -evolution activities under visible light irradiation. Abstract : In the present work, nickel phosphide (Ni12 P5 ) modified graphitic carbon nitride (g-C3 N4 ) nanosheets were synthesized by a simple grinding method. The structural characterization clearly proved that Ni12 P5 nanoparticles were well loaded on the surface of g-C3 N4 nanosheets. The photocatalytic activity of the composites was tested by catalyzing the reduction of water to hydrogen under visible light irradiation. The results demonstrate that Ni12 P5 is an efficient co-catalyst for photocatalytic H2 production of g-C3 N4 nanosheets. The maximum photocatalytic H2 -production rate of 126.61 μmol g −1 h −1 could be obtained by loading 2.0% Ni12 P5 nanoparticles on the surface of g-C3 N4, which is about 269.4 times higher than that of pure g-C3 N4 . It is believed that Ni12 P5 nanoparticles on the surface of g-C3 N4 could act as significant active sites to boost separation of photoexcited electrons and holes and accelerate the H2 -evolution kinetics, thus achieving greatly enhanced hydrogen generation. It is expected that this work could contribute to further experimental investigation for exploiting the low cost, high-efficiency, and environmentally friendly g-C3 N4 -based nanocomposites for photocatalytic H2 production.